2007
DOI: 10.1007/s10544-007-9149-0
|View full text |Cite
|
Sign up to set email alerts
|

Nano-aquarium for dynamic observation of living cells fabricated by femtosecond laser direct writing of photostructurable glass

Abstract: We demonstrate the fabrication of three-dimensional (3-D) hollow microstructures embedded in photostructurable glass by a nonlinear multiphoton absorption process using a femtosecond (fs) laser. Fs laser direct writing followed by annealing and successive wet etching in dilute hydrofluoric (HF) acid solution resulted in the rapid manufacturing of microchips with 3-D hollow microstructures for the dynamic observation of living microorganisms and cells in fresh water. The embedded microchannel structure enables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 31 publications
0
71
0
Order By: Relevance
“…23 It is known that the cell adjusts its swimming path with respect to incident light in a finely tuned manner. 23,24 The loaded cells, wild strain CC-124, were illuminated with blue LED. The cells started to be biased with 1-2 s of time delay after turning on the light, resulting in a shift of the cells to opposite side of the chamber that was demonstrated in the microfluidic chamber (Fig.…”
Section: B Cultivation Of Chlamydomonas Cells In Microfluidic Perfusmentioning
confidence: 99%
“…23 It is known that the cell adjusts its swimming path with respect to incident light in a finely tuned manner. 23,24 The loaded cells, wild strain CC-124, were illuminated with blue LED. The cells started to be biased with 1-2 s of time delay after turning on the light, resulting in a shift of the cells to opposite side of the chamber that was demonstrated in the microfluidic chamber (Fig.…”
Section: B Cultivation Of Chlamydomonas Cells In Microfluidic Perfusmentioning
confidence: 99%
“…Note that other authors have demonstrated that similar approaches can be used with Foturan® (a photoetchable glass). Some of these works are reported in [22] and [23].…”
Section: Initial Patternmentioning
confidence: 99%
“…Although observation along the direction perpendicular to the body motion (side view) has been carried out frequently, there have been few reports on observation along the parallel direction (front view), even though the latter provides a more functional analysis of flagellar movement. The introduction of microorganism suspensions into 3D microfluidic devices showed a potential for increasing the possibility of flexible observation owing to the spatial confinement of biological fluids 10 . However, in the case of microorganisms swimming along a specific direction in a continuous manner, observation efficiency is still not high enough, even when using microfluidic devices, because of the random swimming behavior of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we demonstrate the fabrication of new electrofluidic devices in which designable geometries of electrodes are integrated at the desired positions in glass microchannels by hybrid fs laser microfabrication. The fabricated electrofluidics are applied to nanoaquariums, which are a type of biochip for the dynamic observation and investigation of the function of aquatic microorganisms 10 . The flexible orientation of microorganisms in both the planar and z-directions (parallel and perpendicular to the device surface, respectively) is demonstrated, and the manipulation efficiency is quantitatively analyzed.…”
Section: Introductionmentioning
confidence: 99%